VSL#3 Probiotic Stimulates T-cell Protein Tyrosine Phosphatase–mediated Recovery of IFN-γ–induced Intestinal Epithelial Barrier Defects. Issue 12 (4th November 2016) - Krishnan, Moorthy; Penrose, Harrison M.; Shah, Nilay N.; Marchelletta, Ronald R.; McCole, Declan F.
Abstract : Background: VSL#3 is a probiotic compound that has been used in the treatment of inflammatory bowel disease. T-cell protein tyrosine phosphatase (TCPTP) is the protein product of the inflammatory bowel disease candidate gene, PTPN2, and we have previously shown that it protects epithelial barrier function. The aim of this study was to investigate whether VSL#3 improves intestinal epithelial barrier function against the effects of the inflammatory bowel disease–associated proinflammatory cytokine, interferon-gamma (IFN-γ) through activation of TCPTP. Methods: Polarized monolayers of T84 intestinal epithelial cells were treated with increasing concentrations of VSL#3 to determine effects on TCPTP expression and enzymatic activity. Therapeutic effects of VSL#3 against barrier disruption by IFN-γ were measured by transepithelial electrical resistance and fluorescein isothiocyanate–dextran permeability. A novel TCPTP-deficient HT-29 intestinal epithelial cell line was generated to study the role of TCPTP in mediating the effects of VSL#3. Tight junction protein distribution was assessed with confocal microscopy. Results: VSL#3 increased TCPTP protein levels and enzymatic activity, correlating with a VSL#3-induced decrease in IFN-γ signaling. VSL#3 corrected the decrease in transepithelial electrical resistance and the increase in epithelial permeability induced by IFN-γ. Moreover, the restorative effect of VSL#3 against IFN-γ signaling, epithelial permeability defects, altered expression and localization of the tight junction proteins claudin-2, occludin, and zonula occludens-1, were not realized in stable TCPTP/( PTPN2 )-deficient HT-29 intestinal epithelial cells. Conclusions: VSL#3 reduces IFN-γ signaling and IFN-γ-induced epithelial barrier defects in a TCPTP-dependent manner. These data point to a key role for TCPTP as a therapeutic target for restoration of barrier function using probiotics.